Adenoma prevalence and cancer risk in familial non-polyposis colorectal cancer. Issue 2 (1st February 2002) - Lindgren, G; Liljegren, A; Jaramillo, E; Rubio, C; Lindblom, A
Abstract : Background and aims: Polypectomy in the colon has been shown to prevent colorectal cancer in both the general population and in familial colorectal cancer. Individuals with a family history of colorectal cancer have an increased risk of the disease. Over a period of 10 years, 304 subjects at risk were included in ongoing surveillance with regular colonoscopies. To compile the medical findings and experience generated during this period, a retrospective cross sectional study was performed. Subjects: Subjects were classified into three family groups: families with hereditary non-polyposis colorectal cancer (HNPCC); families with hereditary colorectal cancer (HCC, non-Lynch syndrome); and a third group of families with only empirical risk estimates based on a family history of two close relatives (TCR) with colorectal cancer. Methods: The risk population was studied with regard to age at onset, prevalence, number, cancer risk, size, dysplasia, and distribution of adenomas. A comparison was made within the family groups and with a reference group representing the general population. Results: In total, 195 adenomas and six cancers were detected among 85 individuals. The relative risk of having an adenoma in the whole risk population compared with the general population was 2.6. Subjects from TCR families had most adenomas and HNPCC subjects had the least. A shift from proximal adenomas to distal carcinomas in families with HCC and TCR suggested a higher cancer risk in distal adenomas in these syndromes. HNPCC families showed a younger age at onset and adenomas with a higher degree of dysplasia. In HNPCC, there was a similar localisation of adenomas and carcinomas, suggesting a high risk of cancer in all adenomas. Conclusions: There was clear overrepresentation of adenomas in all three family types compared with the reference population. In HNPCC, we found earlier onset of adenomas and faster progression to cancer. Families with HCC, and even more so TCR subjects, had a later onset and lower risk of cancer from proximal adenomas. Based on these results, surveillance protocols in Sweden have been revised.